String Processing and Information Retrieval: 17th International Symposium, SPIRE 2010, Los Cabos, Mexico, October 11-13, 2010. Proceedings - Chávez, Edgar (Lecture notes in computer science, 2010)
Crowdsourcing and Recommendation -- Querying the Web Graph -- Incremental Algorithms for Effective and Efficient Query Recommendation -- Fingerprinting Ratings for Collaborative Filtering — Theoretical and Empirical Analysis -- On Tag Spell Checking -- Indexes and Compressed Indexes -- Compressed Self-indices Supporting Conjunctive Queries on Document Collections -- String Retrieval for Multi-pattern Queries -- Colored Range Queries and Document Retrieval -- Range Queries over Untangled Chains -- Theory -- Multiplication Algorithms for Monge Matrices -- Why Large Closest String Instances Are Easy to Solve in Practice -- A PTAS for the Square Tiling Problem -- On the Hardness of Counting and Sampling Center Strings -- String Algorithms I -- Counting and Verifying Maximal Palindromes -- Identifying SNPs without a Reference Genome by Comparing Raw Reads -- Dynamic Z-Fast Tries -- Improved Fast Similarity Search in Dictionaries -- Compression -- Training Parse Trees for Efficient VF Coding -- Algorithms for Finding a Minimum Repetition Representation of a String -- Faster Compressed Dictionary Matching -- Relative Lempel-Ziv Compression of Genomes for Large-Scale Storage and Retrieval -- Querying and Search User Experience -- Standard Deviation as a Query Hardness Estimator -- Using Related Queries to Improve Web Search Results Ranking -- Evaluation of Query Performance Prediction Methods by Range -- Mining Large Query Induced Graphs towards a Hierarchical Query Folksonomy -- String Algorithms II -- Finite Automata Based Algorithms for the Generalized Constrained Longest Common Subsequence Problems -- Restricted LCS -- Extracting Powers and Periods in a String from Its Runs Structure -- On Shortest Common Superstring and Swap Permutations -- Document Analysis and Comparison -- A Self-Supervised Approach for Extraction of Attribute-Value Pairs from Wikipedia Articles -- Temporal Analysis of Document Collections: Framework and Applications -- Text Comparison Using Soft Cardinality -- Hypergeometric Language Model and Zipf-Like Scoring Function for Web Document Similarity Retrieval -- Compressed Indexes -- Dual-Sorted Inverted Lists -- CST++ -- Succinct Representations of Dynamic Strings -- Computing Matching Statistics and Maximal Exact Matches on Compressed Full-Text Indexes -- The Gapped Suffix Array: A New Index Structure for Fast Approximate Matching -- String Matching -- Parameterized Searching with Mismatches for Run-Length Encoded Strings -- Fast Bit-Parallel Matching for Network and Regular Expressions -- String Matching with Variable Length Gaps -- Approximate String Matching with Stuck Address Bits -- Erratum -- Erratum to: Range Queries over Untangled Chains.